Resilience as a policy narrative: potentials and limits in the context of urban planning. (17th February 2018) - Béné, Christophe; Mehta, Lyla; McGranahan, Gordon; Cannon, Terry; Gupte, Jaideep; Tanner, Thomas
Abstract : The aim of this paper is to analyse the emergence of the concept of 'urban resilience' in the literature and to assess its potentials and limitations as an element of policy planning. Using a systematic literature review covering the period 2003–2013 and a combination of techniques derived from narrative analysis, we show that diverse views of what urban resilience means and how it is best used (as a goal or as a conceptual/analytical framework) compete in the literature. Underlying these views are various (and sometimes diverging) interpretations of what the main issues are and what forms of policies or interventions are needed to address these issues. Urban planners need to be better aware of these different interpretations if they want to be in a position to use resilience appropriately and spell out what resilience can bring to their work. The review also highlights that the notion of urban resilience often lacks adequate acknowledgement of the political economy of urbanization and consequently does not challenge the status quo which, some argue, is socially unjust and environmentally unsustainable. As such it runs the risk to be seen as simply making marginalized urban communities more resilient to the shocks and inequity created by the current dominant paradigm.